A. SMITH - Events and Urban Regeneration: The Strategic Use of Events to Revitalise Cities - Monclús Fraga, Javier (ZARCH, 2019)
Andrew Smith Event and urban regeneration. The strategic use of events to revitalise cities Londres: Routledge, 2012. 304 páginas. Idioma: inglés ISBN: 9780415581486